Consensus algorithms for peer-to-peer data storage networks - Joshi, Artur (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
Recently blockchain applications became a standard for peer-to-peer (P2P) data storage networks for its security, immutability and decentralization. There are huge number of applications built on blockchain basis from digital currencies to electronic voting and healthcare. As of anonymous nature of blockchain, it has a problem of trust of the nodes of which networks consists. Consensus algorithms are aimed to solve this issue providing protocols which make network data being protected by every single node in a system.